CSA practices implemented and evalauted across the CSV network in 2017 - Bonilla Findji, Osana; Bui Tan Yen; Castellanos, A; Khatri-Chhetri, Arun; Kimeli, Philip; Martínez Barón, Deissy; Martínez, J.; Ortega, Luis A.; Ouédraogo, M.; Radeny, Maren A.O.; Recha, John W.M. (2018)
This progress report summarizes the CSA practices, technologies and services implemented and/ or evaluated in 2017 across the CCAFS Climate-Smart villages network